Informing society in African, Caribbean and Pacific countries : developing unlikely partnerships - Mc Bean, Bridget (2005)
Suggests that in order to benefit from the opportunities envisaged by the World Summit on the Information Society, developing countries need to work with unlikely partners in the creation of integrated information and communication policies.